What Can Sociogenomics Learn from Social By Nature? A review of social by nature, by Catherine Bliss. (2nd October 2018) - Daw, Jonathan; Chapman, Alexander; Evans, Megan
ABSTRACT: Social by Nature, the recent book by Catherine Bliss on the development and state of the field of sociogenomics, is far from perfect. Yet, this flawed book levies a mixture of erroneous and compelling questions about the state of the field of sociogenomics, many of which we as a field would benefit from considering: How should we bring the environment back in the post-GWAS era? How do the publication and funding incentives of our field influence the evolution of our research agenda? What role should social scientific theory play in motivating our research and interpreting our findings? How can we promote greater diversity in our research community and subjects? And how can we work to better control media and popular narratives of our research? The authors do not attempt to answer all of these questions definitively, but do argue that we as a field must grapple with them seriously to ensure that our ideals and reality as a field are more congruent.